Deformation behavior of typical inclusions in GCr15 during hot rolling process (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
Non-metallic inclusions significantly impact the lifespan of bearing steel. Investigating the deformation behavior of these inclusions during the rolling process is crucial for controlling their shape and size in production. This study focuses on GCr15 bearing steel, a representative grade of bearing steel, and utilizes the finite element software ABAQUS to simulate the deformation of Al2O3 inclusions, MnS inclusions, and Al2O3-MnS composite inclusions after hot rolling of GCr15 steel. The findings indicate that when the size of inclusions is within 10 µm, their type and shape have a more significant impact than variations in size. Among them, Al2O3-MnS composite inclusions exhibit the least harm to the steel matrix. The stress concentration of Al2O3 inclusions will appear on the MnS cladding layer, which can slow down the occurrence of cracks. Additionally, the aspect ratio of MnS inclusions decreases after rolling, diminishing its influence on the steel matrix's anisotropy. Simultaneously, composite inclusions can harmonize the deformation capabilities of the inclusions and the steel matrix, thereby minimizing the likelihood of void formation. Consequently, in the smelting process, it is beneficial to modify inclusions into regular circular shapes and form composite Al2O3-MnS inclusions to mitigate their detrimental effects on the steel matrix.
Keywords: Hot rolling; Complex inclusions; Stress concentration; Strain difference; Finite element simulation